The Central Role of In-Formation in the Age of Artificial Intelligence and its Significance to Legal Personhood - Simanjuntak, Mardohar Batu Bornok; P Moeliono, Tristam (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2024)
Artificial intelligence (AI) can be understood from an epistemological standpoint, specifically in relation to the concept of legal personhood. It has evolved into a stronger version with broader capabilities, surpassing its predecessors, particularly Artificial Narrow Intelligence (ANI). This rapid advancement has significant consequences, not to mention its increasing problem-solving ability–an essential characteristic of intelligence. To determine its legal status, AI must meet specific criteria. Generative AI, such as large language models (LLMs), serves as a warning sign, as Yuval Noah Harari argues, radically altering how humans cooperate. Harari maintains that social constructs have historically relied on human-to-document intersubjective interaction, mediated by bureaucracies. The latest developments, however, shift this relationship toward document-to-document interaction, transforming the nature of information. Instead of being merely a collection of data (‘inform-ation’), information now serves as the fundamental backbone of social institutions (‘in-formation’). From a periscopic perspective, as discussed by the authors, the discrepancy between the real and the metaversal expands AI’s role in everyday human activities. The authors propose a special legal personhood status for AI, considering its emerging analytic a priori capabilities. However, while AI remains in the later stages of its development, this possibility introduces mitigated risks that require further analyses.